Research and practice of flipped classroom based on mobile applications in local universities from the perspective of self-determination theory - Hao, Yan'e; Lan, Yongqiang (Frontiers in Psychology, 2023)
Self-determination theory is a psychological theory proposed by American psychologists and is widely used in research in the field of education. Mobile applications are gradually changing the traditional classroom communication mode between teachers and students with their intelligent, portable, and humanized operation. Deep integration of information technology and education teaching, promoting mobile applications into the teaching process, facilitating local colleges and universities to better achieve the cultivation goal of high-quality application-oriented talents, and exploring a new learner-centered classroom teaching model are hot issues of current research in the education field. The flipped classroom and mobile application were effectively combined, and a flipped classroom model based on mobile application was proposed and implemented. Based on self-determination theory, this study investigates the current situation of students' basic psychological needs satisfaction and classroom satisfaction under the flipped classroom model based on mobile applications and explores the relationship between the students' basic psychological needs satisfaction and classroom satisfaction. A total of 151 local college students in different professional fields participated in the questionnaire survey. The research results reveal that in the flipped classroom model based on mobile applications, the students' basic psychological needs satisfaction and classroom satisfaction are at a high level, and the two are significantly positively correlated. Therefore, the students' basic psychological needs affect their satisfaction with the classroom, which provides some references for the smooth implementation and further promotion and application of the classroom teaching model.